2014
DOI: 10.1021/om500918y
|View full text |Cite
|
Sign up to set email alerts
|

Organolanthanide Complexes Supported by Thiazole-Containing Amidopyridinate Ligands: Synthesis, Characterization, and Catalytic Activity in Isoprene Polymerization

Abstract: Neutral bis(alkyl)-organolanthanide complexes supported by tridentate {N − ,N,N} monoanionic 5-methylthiazole-or benzothiazoleamidopyridinate ligands have been prepared and completely characterized: (L Thia Me 2 )Ln(CH 2 SiMe 3 ) 2 [Ln = Lu 3+ (3), Er 3+ (7), Yb 3+ (8)] and (L BnTh Me 2 )Lu(CH 2 SiMe 3 ) 2 (5). Similarly to related Y 3+ systems, the nature of the thiazole unit controls the ultimate catalyst stability in solution. In the diamagnetic Lu 3+ complex 5, a progressive and complete rearrangement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Lutetium(III) complexes have wide range applications in catalysis in the past few years [4][5][6]. Some directly related structures of the title structure have been reported [3,[7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Lutetium(III) complexes have wide range applications in catalysis in the past few years [4][5][6]. Some directly related structures of the title structure have been reported [3,[7][8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the electrochemical behavior of Sc 3 C 2 @I h -C 80 was markedly changed by the radical addition, but the absorption spectra of the pristine and the derivative are both featureless. These results suggested that the unpaired electron of The reactions of (µ-H) 3 Re 3 (CO) 11 (NCMe) with Sc 2 @C 82 -C 3v (8), Sc 2 C 2 @C 80 -C 2v (5), Sc 2 O@C 82 -C s (6), C 86 -C 2 (17), and C 86 -C s (16) have been carried out to produce facecapping cluster complexes. The Re 3 triangles were found to bind to the sumanene-type hexagons (cf.…”
Section: Indenyl Compoundsmentioning
confidence: 99%
“…[103] M a n u s c r i p t The influence of the ligand type, metal ion, and activator(s) on the ultimate catalyst activity and selectivity has been discussed. [11] In a related study, it has been pointed out that precisely controlling the stereochemistry of a copolymerization by a single catalyst, and achieving copolymers with predicted sequences, is often a challenging project in organometallic and macromolecular sciences. In this context it was discovered that the [110]…”
Section: Indenyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, our group has been extensively working on the preparation of multidentate heteroleptic N‐ligands and their related κ 3 {N,N,N}M 3+/4+ coordination compounds (or κ 3 {N,C,N}M 3+/4+ /κ 3 {N,N,C}M 3+/4+ organometallics) based on highly electrophilic metal ions (from group IV elements of the periodic table or from lanthanides, ) for applications in homogeneous catalysis. In a recent report, we have described the synthesis, characterization and catalytic application of a series of Zr IV /Hf IV alkyl/amido complexes stabilized by a tridentate N‐ligand containing a benzoimidazole fragment .…”
Section: Introductionmentioning
confidence: 99%